A study on two R-phase transformations in intermediate temperature aged Ni-rich TiNiFe-based shape memory alloys. (May 2021) - Tu, Chun-Hsiang; Wu, Shyi-Kaan; Lin, Chieh; Huang, Bo-Yang
Abstract: The effects of intermediate temperature aging on two-stage R-phase transformation behavior exhibited in Ti50-x Ni48+x Fe2 (x = 0.5 and 1.5) SMAs were investigated. In Ti48.5 Ni49.5 Fe2 SMA, no transformation occurred in the as solution-treated state, and B2↔R1 transformation was induced by Ti3 Ni4 precipitates when the specimens were aged at 350 °C. When the specimens were aged at 450 °C, a two-stage R-phase transformation, B2↔R1 and B2↔R2, appeared. The B2↔R1 transformation, induced by Ti3 Ni4 precipitates, occurred at higher temperature, whereas the B2↔R2 transformation, related to the Fe content in the matrix, occurred at lower temperature. The Ti49.5 Ni48.5 Fe2 SMA possesses a two-stage B2↔R2 ↔B19′ transformation in the as solution-treated state. When Ti49.5 Ni48.5 Fe2 specimens are aged at 350 °C/450 °C, R2 →B19′ is suppressed and B2↔R1 appears as the aging time increases with R2 ↔B19′ disappearing and B2↔R1 appearing earlier when the aging temperature is higher. The two-stage R-phase transformation behavior exhibited in these two aged TiNiFe-based SMAs is a compromise between Ti3 Ni4 precipitation and the decrease in Ni content and increase in Fe content in the matrix during the aging process. Highlights: Ni-rich TiNiFe2 SMAs can exhibit two R-phase transformations after aging. R-phase transformation with higher temperature is induced by Ti3 Ni4 precipitates. R-phase transformation with lower temperature is related to matrix's Fe content. Two R-phase transformations are a compromise of precipitates and composition change.